Portable oceanic solutions for enhanced IoT-based desalination and salt extraction (POSEIDON) - Randi Agustio; Onky Prilianda Putra; Dananjaya Ariateja; Refino Maulana Hansbullah Subarkah; H. A Danang Rimbawa (Institute of Computer Science (IOCS), 2025)
The clean water crisis remains a significant challenge in many remote areas, particularly on small islands in Indonesia where freshwater resources are limited. Desalination technology offers a promising solution; however, conventional methods often face obstacles such as high energy consumption, costly operations, and limited real-time water quality monitoring. This study aims to design and evaluate a distillation-based desalination device integrated with Internet of Things (IoT) technology, called POSEIDON. The system utilizes solar energy and heating elements to support the distillation process and is equipped with pH, TDS, ultrasonic, and water level sensors connected to the Blynk application for real-time monitoring and alert notifications. Testing was conducted over 10 hours under both daytime and nighttime conditions. Results show that the distilled water had pH values ranging from 7.01 to 7.51 and PPM values from 798 to 588.38. One-way ANOVA indicated no statistically significant variation (p > 0.05), demonstrating consistent system performance. The average volume of fresh water produced was 0.403 liters from 0.7 liters of seawater, with an average salt yield of 23.1 grams. POSEIDON exhibits good energy efficiency and portability, and it can operate at night. Nevertheless, improvements are needed in production capacity and water quality. Overall, POSEIDON presents a viable and sustainable solution to meet clean water needs in remote, water-scarce regions.